KEANEKARAGAMAN SPESIES DAN PENDUGAAN CADANGAN KARBON ATAS PERMUKAAN PADA TIPE PENGELOLAAN LAHAN DUSUNG NEGERI RUTONG, AMBON - Irwanto, Irwanto; Sahupala, Andjela; Siruru, Herman (Universitas Pattimura, 2023)
Dusung is traditional land management in Maluku by planting various plant species in the same area. Factors such as intensive land management, selection and combination of plant species, vegetation structure, topography, soil, and others influence the economic and ecological productivity of dusung. Ecological productivity affects the biomass content, which indicates the potential for carbon absorption in the land. The method used in this research is direct measurements in the field of several carbon pools specifically for aboveground biomass. Data collection was guided by Indonesian National Standards (SNI) 7724-2019 concerning field measurements for estimating forest carbon stocks. The research result showed that the diversity of vegetation species in Dusung Rutong Village at all growth levels in the moderate category tends to be low, dominated by fruit plants such as Durian (Durio zibethinus). Tree-level species diversity is moderate because the community controls the species that grow on Dusung land. The total aboveground carbon stocks in Dusung Rutong Village are 106.424 tonnes/ha, consisting of trees 100.673 tonnes/ha, undergrowth 1.708 tonnes/ha, litter 1.124 tonnes/ha, necromass 0.042 tonnes/ha and bamboo (Schizostachyum brachycladum) 2.877 tonnes/ha while the potential for equivalent carbon dioxide (CO2) absorption of 390.221 tonnes/ha.